2017
DOI: 10.3389/fimmu.2017.00902
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Surgery Impair Blood–Brain Barrier and Cognitive Function in Mice

Abstract: Blood–brain barrier (BBB) dysfunction, e.g., increase in BBB permeability, has been reported to contribute to cognitive impairment. However, the effects of anesthesia and surgery on BBB permeability, the underlying mechanisms, and associated cognitive function remain largely to be determined. Here, we assessed the effects of surgery (laparotomy) under 1.4% isoflurane anesthesia (anesthesia/surgery) for 2 h on BBB permeability, levels of junction proteins and cognitive function in both 9- and 18-month-old wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 65 publications
5
158
0
3
Order By: Relevance
“…A number of molecular mechanisms have been proposed to account for the cognitive decline induced by sevoflurane, among which the neuroinflammation induced by anesthesia combined with surgery is generally believed to serve as the trigger and is supported by several reports . For instance, Yang et al reported that anesthesia/surgery impaired the permeability of the blood–brain barrier, and caused an elevated production of interleukin‐6 in an age‐associated manner, accompanied by the prominent deficits in cognitive functions . Furthermore, data generated from both human patients and model animals indicated that sevoflurane administration was related to the levels of pro‐inflammatory mediators, such as tumor necrosis factor‐alpha and interleukin‐6 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A number of molecular mechanisms have been proposed to account for the cognitive decline induced by sevoflurane, among which the neuroinflammation induced by anesthesia combined with surgery is generally believed to serve as the trigger and is supported by several reports . For instance, Yang et al reported that anesthesia/surgery impaired the permeability of the blood–brain barrier, and caused an elevated production of interleukin‐6 in an age‐associated manner, accompanied by the prominent deficits in cognitive functions . Furthermore, data generated from both human patients and model animals indicated that sevoflurane administration was related to the levels of pro‐inflammatory mediators, such as tumor necrosis factor‐alpha and interleukin‐6 .…”
Section: Discussionmentioning
confidence: 92%
“…For instance, a study on a group of older adults undergoing major non‐cardiac surgeries determined that risk factors for POCD included carrying the apolipoprotein E4 genotype, using highly anticholinergic or sedative‐hypnotic agents before surgery, and receiving anesthetics . Consistently, it was found in animal models that general anesthetics indeed initiated neurotoxic events and caused a number of alterations to the hippocampus, the essential structure in cognitive functions . Therefore, cautious choice of anesthetics, as well as better operative techniques, have been proposed as strategies to prevent POCD.…”
Section: Introductionmentioning
confidence: 99%
“…Taking incidence into account, we therefore used ligation of the CCA to induce CH in ageing rats in this study. As it is di cult to separate clinical anaesthesia and surgery, and our main purpose was to explore the combined effects of the two factors, no separate anaesthesia group was used, which is consistent with most recent studies [34][35][36].…”
Section: Discussionmentioning
confidence: 93%
“…The method is based on the established BBB dye-injection assay with slight modi cation [28,29]. Speci cally, 6 h after surgery, each mouse was injected intravenously through tail veins with 100 µl 10-kDa dextran Texas Red (Invitrogen, D1863 Spectrophotometric quanti cation of extravascular 10-kDa dextran Texas Red was carried out with extracts of the hippocampus and prefrontal cortex at 6 hours after surgery.…”
Section: Bbb Permeability Assaymentioning
confidence: 99%
“…The breakdown of blood-brain barrier (BBB) has been reported to be associated with delirium and perioperative neurocognitive disorders [35,36], herein we employed a well-established dye injection assay to investigate the integrity of BBB [28,29] under the treatment of surgery/anesthesia with or without NPD1.…”
Section: Npd1 Prophylaxis Alleviates the Leakage Of Bbb Induced By Sumentioning
confidence: 99%